STUDY ON WAR AND HUNTING WEAPONS IN CENTRAL ANDINA AREA. DESCRIPTION AND USE OF THRUSTING AND CUTTING WEAPONS - Chamussy, Vincent (2014)
All types of weapons were not used in the same way and at the same time during the prehistory of the Central Andean Area. Throwing weapons have been used mainly for hunting and ritual. Thrusting weapons have been war weapons par excellence, and hand to hand fight the preferred type of fight. Among thrusting weapons, the club, although dreadful in action, always symbolized power and prestige, while among cutting weapons, the axe became the tool of sacrifice called tumi, whereas the knife became the dagger.